Reaching racial/ethnic and sexual and gender minorities with HIV prevention information via social marketing. (February 2022) - Marshall, Brittany; Salabarría-Peña, Yamir; Johnson, Wayne; Moore, Leo
Abstract: The Pre-exposure Prophylaxis, Data to Care, Implementation, and Evaluation (PrIDE) multi-site demonstration project utilized a cluster evaluation approach and identified six funding recipients that evaluated similar media evaluation questions (Baltimore, Los Angeles County, Lousiana, Michigan, New York City, and Virginia). All of the evaluated social marketing campaigns were developed in collaboration with health department staff, external marketing firms, and community advisory boards (CAB) aiming to produce changes in PrEP outcomes by reaching racial/ethnic and sexual and gender minorities. Jurisdictions demonstrated changes in PrEP awareness, knowledge, willingness to take PrEP, and/or PrEP literacy following initiation of the campaigns. In data from four sites, PrEP awareness significantly increased from 72 % at baseline to 86 % at mid-project, and to 90 % post-campaigns. The campaigns illustrate the importance of partnerships and stakeholder engagement, audience segmentation, and intentional evaluation planning. As PrEP services mature, evaluating PrEP demand and PrEP use resulting from campaigns, will be necessary. Also, future campaigns for racial/ethnic and sexual and gender minorities should identify the best channels to reach each group based on their input, disaggregate data by priority group, and determine campaign effectiveness.